Growing media influence on the growth and development of Rosa hybrida - Mohammad Moneruzzaman, Khandaker; Noor Afiza, Badaluddin; Mahmoud Dogara, Abdulrahman (2020)
A study was carried out to investigate the effects of various growing media on the reproductive and vegetative rose plants growth. The rose seedling was collected from a commercial nursery, located at Kuala Terengganu, Malaysia. Five growing media (Bris soil + perlite as control, agropolis media, microbial media, garden soil media, and Garden soil + poultry manure) were used. The tryout was set in accordance with Completely Randomized Design (CRD) with 4 replicates. Garden soil with addition of poultry manure showed the best growing media for the production of Rosa hybrida in terms of the number of flowers, total soluble solids content of leaf, the diameter of flower, the length of petal, the number of petals, the length of root and the carotene content of the rose petal. Flower longevity in potted rose plants was also highest in garden soil plus poultry manure media. There was a linear correlation among flower number, leaf TSS content and between flower longevity with leaf TSS content in potted rose plants. Results of the study provided how the growth and development quality of cut flower production in Rosa hybrida could be improved.